Consumption of minas frescal cheese may be a source of human infection by Campylobacter jejuni (Bioscience Journal, 2020)
Campylobacter spp. is an emerging pathogen that causes gastroenteritis in humans and the consumption of dairy food can characterize sources of infection. We aimed to verify the viability and a presence of transcripts associated with characteristics of virulence and adaptation of C. jejuni isolated from Minas Frescal cheeses, produced with contaminated milk and stored under refrigeration for up to ten days. The samples were analyzed for bioindicators, Campylobacter spp., pH, acidity, moisture and sodium chloride. Campylobacter spp. recovered were evaluated for the production of transcripts of: ciaB, dnaJ, p19 and sodB. The results were correlated with the viability of C. jejuni and changes in their transcriptome. Storage at low temperatures reduced C. jejuni from the first to the fourth day. The variations in humidity, pH and acidity influenced the decreasing of C. jejuni. There was a reduction in transcripts' production of the four genes, more pronounced on the fourth day, indicating the inability of the microorganism to perform its metabolic activities, due to the conditions of injury. Despite the presence of mechanisms of virulence and adaptation, C. jejuni could not remain viable four days after production. However, consumption of fresh cheese contaminated with Campylobacter jejuni can be a source of infection when consumed up to four days after production.